A history of the Roman world from 753 to 146 B.C. - Scullard, H. H. (Howard Hayes), 1903-1983, author. Link
1 online resource (iv, 500 pages).
Keywords: A History of the Roman World from 753 to 146 B.C. (1969) examines the rise of Rome from a small city-state among many to its conquest and unification of Italy and the founding of its overseas Empire. It covers in detail Rome's struggle with Carthage for supremacy, as well as Rome's political, economic and social life during the period.